1996
DOI: 10.1128/jvi.70.3.1668-1677.1996
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and replication of adeno-associated virus type 2 as well as vector DNA sequences from recombinant plasmids containing deletions in the viral inverted terminal repeats: selective encapsidation of viral genomes in progeny virions

Abstract: The adeno-associated virus type 2 (AAV) genome can be successfully rescued from recombinant plasmids following transfection in adenovirus-infected human cells. However, following rescue, the AAV genome undergoes preferential replication and encapsidation, whereas little replication and packaging of the vector DNA sequences occur. In view of the crucial role in the rescue, replication, and packaging of the proviral genome played by the AAV inverted terminal repeats (ITRs), which consist of a palindromic hairpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 46 publications
(90 reference statements)
3
64
0
Order By: Relevance
“…The effective replication and encapsidation of the DD construct indicates the crucial role that the D sequence plays in these processes. This is consistent with observations that deletion of D sequences abolishes AAV replication and packaging (39,40,43). In addition, in vitro Rep68 binding and nicking assays are affected by mutant substrates that altered the trs sequence or spacing between A and D elements (23,34).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The effective replication and encapsidation of the DD construct indicates the crucial role that the D sequence plays in these processes. This is consistent with observations that deletion of D sequences abolishes AAV replication and packaging (39,40,43). In addition, in vitro Rep68 binding and nicking assays are affected by mutant substrates that altered the trs sequence or spacing between A and D elements (23,34).…”
Section: Discussionsupporting
confidence: 92%
“…Rescue involves resolution of the ITR. The ITRs are the AAV rescue substrates and replication origins (39)(40)(41). Since the DD plasmids contain only a single modified ITR and replicated via an AAV mechanism in the presence of Rep proteins, we tested this substrate for the ability to rescue in vivo.…”
Section: Construction Of a Modified Aav Itr With Dd Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following purification and mass spectrometry, the cellular protein binding with the ssD[ϩ] sequence was found to have partial amino acid homology to NF-B-repressing factor (NRF), a negative regulator of transcription (NRF) (17). Since both the cellular proteins binding with either the ssD[Ϫ] or ssD[ϩ] sequence have the potential to inhibit transgene expression mediated by ssAAV vectors and since we have previously reported that the removal of the D sequences from the viral genome impairs rescue, replication, and encapsidation of AAV DNA (18)(19)(20), we wished to examine whether restoration of one D sequence in the ssAAV genome might not only restore rescue, replication, and encapsidation but also enhance transgene expression from ssAAV vectors. We report here that the ssD[ϩ]-sequence-substituted ssAAV genomes could be successfully packaged into rAAV vectors and that the transduction efficiency of these vectors was significantly higher than that of conventional ssAAV vectors.…”
mentioning
confidence: 99%